Pariwisata Ekologi Untuk Memperkenalkan Budaya Rumpun Melayu - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT: Southeast Asia that occupied by most of Malay stock can be developed an international destination for tourism, either for social, economy, or culture. What with geologically and geographically the natural setting is very beautiful and the influence to the culture behavior of the people has been created an interdependency that can be developed easily for attractive ecological tourism. How the people to be influenced or modified third natural setting, has been created a characteristic natural behavior of the Malay stock that not be met in all over the world. The natural setting that so beautiful and strong influence to the people behaviour has been created so may characteristic of the Southeast Asia engineering built-ups, and represent the principle the natural resource. But the influence of the softificated lives, there are so many capabilities heritage are not appreciated. Even though, all kinds of wise value are easy to be met in all over southeast especially in Indonesia that cultural behavior is growing up on the same ancestor cultural roots. The natural behavior that still lives based on this natural setting can be developed for ecological tourism in the frame of the characteristic Malay stock cultural.